Synthesis of Nitrogen‐Doped Electrospun Carbon Nanofibers as Anode Material for High‐Performance Sodium‐Ion Batteries. Issue 11 (30th August 2016) - Chen, Chen; Lu, Yao; Ge, Yeqian; Zhu, Jiadeng; Jiang, Han; Li, Yongqiang; Hu, Yi; Zhang, Xiangwu
Abstract: Nitrogen‐doped carbon nanofibers (CNFs) were synthesized using a facile electrospinning technique with the addition of urea as a nitrogen‐doping agent. The amount of urea was selectively adjusted to control the degree and effectiveness of N‐doping. The morphology of N‐doped CNFs was investigated by scanning electron microscopy, transmission electron microscopy, and X‐ray diffraction, whereas their electrochemical performance was studied using cyclic voltammetry and galvanostatic charge–discharge experiments. The nitrogen content of N‐doped CNFs increased significantly from 11.31 % to 19.06 % when the doping amount of urea increased from 0 % to 30 %. N‐doping also played an important role in improving the electrochemical performance of the CNFs by introducing more defects in the carbon structure. Results showed that N‐doped CNFs with the highest nitrogen content (19.06 %) exhibited the largest reversible capacity of 354 mAh g −1 under a current density of 50 mA g −1 ; and when the current density was increased to 1 A g −1, a capacity of 193 mAh g −1 was still maintained. It is, therefore, demonstrated that N‐doped CNFs have great potential as suitable sodium‐ion battery anode material. Abstract : The benefits of urea in energy : Urea, a low‐cost precursor was utilized to enhance the nitrogen content in the carbon nanofibers. The as‐prepared carbon nanofibers show high nitrogen content and enhanced electrochemical performance as sodium‐ion battery anode material.